A "Model to Model" Collaborative Perception Methodology for Distributed Design. (1st June 2014) - Wan, Neng; Du, Ke; Mo, Rong; Xie, Gongnan
Abstract : To solve the problem of collaborative engineering changes of models distributed in heterogeneous design platforms, a "model to model" perception methodology is proposed in this paper. A self-management collaborative architecture is presented by peer to peer architecture and multiagent system. The network addresses correlation between heterogeneous platforms is built up by the perception router ontology. In the same way, the correlation between design models is described by the feature relation ontology. The design changes are encapsulated by the model modification ontology. Along with the ontology above, the design change search method is devised to catch the geometric changes; the influence search method is proposed to discover the influenced design feature and the design change adapting method is used to preserve the correlation coherence after perception. Through the work, the conventional design perception mode among designers has transformed into direct perception among models instead.